ANALISIS KINERJA KEUANGAN PT UNILEVER INDONESIA TBK TAHUN 2022-2023 MENGGUNAKAN RASIO PROFITABILITAS DAN LIKUIDITAS - Alya Kanaya Alfita; Sri Rahayu; Setiawati Setiawati; Rahyuni Puspita Sari; Humaira Athaya Rana (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This research is focused on examining the financial activities of PT Unilever Indonesia Tbk during the years 2022 and 2023 by utilizing profitability and liquidity ratios. The goal of this analysis is to assess how well the company can produce earnings and fulfill its short-term financial responsibilities. The approach taken involves descriptive quantitative research, drawing on secondary data from the organization’s financial statements. The analysis employs several financial ratios, including Return on Assets (ROA), Return on Equity (ROE), Current Ratio, and Quick Ratio to analyze the company's financial movements. The results of this study are expected to shed light on the financial health of the company and provide a foundation for evaluation. Additionally, this study aims to deliver valuable insights for investors, management, and other interested parties. The findings may also be utilized as a reference for subsequent research focused on analyzing financial performance. This research is expected to support better financial decision-making and contribute to improved company performance in the future.